Negative interest rates, excess reserves and tiering of the ECB: How heavily are banks burdened? - Jens Klose (Wirtschaftsdienst)
Abstract The European Central Bank (ECB) reduced its deposit rate into negative territory in June 2014. It has been reduced further in several steps to reach today’s level of −0.5%. Banks are increasingly facing problems investing their deposits without taking great risks and avoiding nominal depreciation. This article shows, however, that the deposit rate has never been the effective lower bound for deposits at the ECB and, moreover, the decision in September 2019 to introduce the tiering programme increased the average deposit rate rather than decreased it as one would have supposed. With this programme, the ECB has relaxed the situation, even though banks in the euro area make different gains.